Business study mission : Ireland cultural intelligence, Huawei Technologies Co. Ltd - Chen, Fang (2010)
This project paper is based on the theme "Cultural Intelligence: Doing Business In and With Ireland". We examined the cultural challenges of doing business in Ireland, and the strategies adopted for addressing these challenges. The specific company being studied in this paper is Huawei Technologies, an emerging leader in telecommunication network solutions. Originated from China, Huawei is a Chinese multinational (MNC) pursuing an aggressive internationalization strategy and is now strategizing to enter the Irish market. The paper discusses about the Irish cultural landscape with a comparison to the Chinese culture. It also explores Huawei's business strategies and organizational capabilities and draw out the challenges that it may face in Ireland, with a focus on marketing and employee management. Finally, it concludes with some key imperatives and recommendation to build and sustain its position in the Irish market.